1994
DOI: 10.1542/peds.93.5.814
|View full text |Cite
|
Sign up to set email alerts
|

Infant Sleep Position and Risk for Sudden Infant Death Syndrome: Report of Meeting Held January 13 and 14, 1994, National Institutes of Health, Bethesda, MD

Abstract: Objective. To evaluate the current knowledge on the relationship between infant sleep position and sudden infant death syndrome (SIDS), and to determine how the information can be used to guide further activities in the United States. Methods. Data from international vital statistics, epidemiologic studies of SIDS risk factors, and studies of outcomes of public health interventions that advocated nonprone sleeping to reduce the risk for SIDS were discussed at a meeting held by the National Insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
3

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(14 citation statements)
references
References 0 publications
0
11
0
3
Order By: Relevance
“…The evidence that in several countries the recommendation to avoid this sleeping position in the first year of life has been accompanied by a significant reduction in SIDS rate is per se a strong demonstration that the prone position has a role in SIDS development [10][11][12][13][14]. Several well conducted epidemiological studies have clearly shown that, compared to the supine position, the prone position is associated with a 1.7-12.9-fold increased risk of SIDS [36].…”
Section: Present Hypothesis On Sudden Infant Death Syndrome (Sids) De...mentioning
confidence: 99%
See 2 more Smart Citations
“…The evidence that in several countries the recommendation to avoid this sleeping position in the first year of life has been accompanied by a significant reduction in SIDS rate is per se a strong demonstration that the prone position has a role in SIDS development [10][11][12][13][14]. Several well conducted epidemiological studies have clearly shown that, compared to the supine position, the prone position is associated with a 1.7-12.9-fold increased risk of SIDS [36].…”
Section: Present Hypothesis On Sudden Infant Death Syndrome (Sids) De...mentioning
confidence: 99%
“…First of all, the evidence is that only a low number of children experiencing ALTE or BRUE die from SIDS (0-7%). Moreover, while the incidence of SIDS has decreased after the introduction of recommendations for safe infant sleeping, the incidence of ALTE has remained unchanged or even increased [10][11][12][13][14]. ALTE, BRUE and SIDS, although disorders of the first year of life, differ significantly in age-at-event.…”
Section: Apparent Life-threating Event (Alte) and Brief Resolved Unex...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the late 1980s and early 1990s researchers in several European countries and New Zealand found many SUIDs were linked to the prone sleep position, which was followed by mass public health campaigns promoting “Back to Sleep”, whereby parents and care givers were instructed to place their infants in a supine or face up position to sleep [ 3 5 ]. These strategies led to a dramatic reduction in infant deaths and increased scrutiny of the sleep environment in other countries.…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…
Although the incidence of sudden infant death syndrome in the United States has declined in recent years, 1 the rate of decline continues to lag substantially behind other industrialized countries where SIDS prevention initiatives have been implemented. 2 The study by Skadberg et al 3 in this issue of The Journal provides yet another excellent example of the remarkable long-term success of a national campaign aimed at avoidance of prone sleeping and decreased SIDS incidence. The authors demonstrated a 98% decrease in prone sleep positioning and a 91% decrease in SIDS rate in a demographically representative county of Norway.
…”
mentioning
confidence: 98%